SIKAP MASYARAKAT TERHADAP POLITIK UANG PADA PEMILIHAN KEPALA DAEARAH SERENTAK TAHUN 2024 KABUPATEN MUNA BARAT - Muhammad Ishak Syahadat; Iriyani Astuti Arief; La Ode Efrianto (Journal Publicuho, 2023)
This research purpose is to find out the people’s attitudes about money politics in the simultaneous regional head elections of 2024, especially in the villages of Barangka, Lapolea, and Sawerigadi in the Barangka District of the West Muna Regency. This research uses the theory of money politics to find out people’s attitudes in the selection of regional head candidates, whether by carrying out various forms of money politics such as; buying votes, giving personal goods, services and events, giving group goods, and pork barrel projects. It’s interesting to know this because, in the Barangka district, voters typically abstain from casting ballots, if they receive no benefits. The data collection technique is used by distributing questionnaires, literature reviews, and documentation with data analysis techniques which consist of three stages, they are; data reduction, data presentation, and conclusion. The research results found that a significant amount of people were received money or other goods from candidates competing in the legislative and regional head elections in the 2024 elections. About thirty percent (30%) of the people in the Barangka District receive money or gifts given by the candidates. This percentage is very high considering that the people in Barangka District are traditional voters who have not been much influenced by technological and information advances. Money politics typically focuses on voter groups in the 25-30 age range and acts as a success team to distribute money from candidates to the public.